PENGARUH JAMBU BIJI MERAH TERHADAP KADAR Hb SAAT MENSTRUASI PADA MAHASISWI DIII KEBIDANAN STIKES MUHAMMADIYAH LAMONGAN - Sulistiyowati Sulistiyowati (Universitas Aisyiyah Yogyakarta, 2015)
The aim of research to determine the effect of guava on Hb levels during menstruation. The study design used Pre-Eksperiment method with one group pre test post-test design. The population are all sophomore of DIII Kebidanan Study Program in STIKES Muhammadiyah Lamongan. Sample taken by purposive Sampling technique. Data taken with observasion and analyzed using Paired T-Test. The result showed that guava was influence Hb levels during menstruation with p=0,000.Keywords: haemoglobin, guava, menstruation, anemia